Kompetensi Pedagogik Guru PPKn dalam Proses Pembelajaran di SMP Negeri 1 Painan Kabupaten Pesisir Selatan - Indri Okta Sari; Junaidi Indrawadi; Al Rafni (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2019)
Abstract Teachers must possess and master pedagogical competencies in realizing effective, creative, fun, and meaningful learning for students seen from ten aspects of pedagogic competence. But in the learning process students pay less attention to learning because the teacher is less attractive and is watching in providing learning. This study aims to see the description of the pedagogical competencies of PPKn teachers in the learning process in Painan 1 Middle School in South Coastal District viewed from ten aspects of pedagogic competence. This study uses a Quantitative Descriptive approach to see, describe the situation, and as it is in the field. The location of this study is in the Painan 1 Middle School in South Coastal District. The population of this study was students of class VIII and IX at the Painan 1 Middle School in South Coastal District consisting of 461 students. The sampling technique uses Sample random sampling with the number of respondents 82 people using the Slovin formula. Data collection in this study is 40 questionnaires by using a Likert Scale. The data analysis used is descriptive statistical analysis with a percentage count. Based on the results of the study, overall the pedagogical competence of the PPKn teachers in the learning process in Painan 1 Middle School in South Coastal District was TCR obtained 78.95%. So that it can be concluded that the answers of class VIII and IX students seen from ten aspects of pedagogical competence are good.